Aprendizagem Online em Ambiente Empresarial - Estudo de Caso de Gamificação de Atividades em Moodle para Funcionários de Restauração - Tiago Mendes Vieira (2022)
More and more, online training is a resource widely used in professional environments. It's effective in training employees at various levels, from scientific to attitudinal. The concepts of Game-based learning and Gamification introduce a new education paradigm in these existing training plans. The increase in motivation and commitment to tasks is the main motivator for the adoption of techniques such as gamification. These new methods have the aim of making learning more attractive, captivating and effective. In this case study of a restaurant company, an investigation is carried out that involves the implementation and analysis of the impact of gamification. This is done through the introduction of a gamification plugin and new training content on an online platform and the subsequent collection of qualitative and quantitative data. The objective of this implementation is to test the impact of the approach on an outdated training plan with content that is difficult to motivate and interest.